1984
DOI: 10.1042/bj2200539
|View full text |Cite
|
Sign up to set email alerts
|

A chromosomal phosphoprotein is preferentially released by mild micrococcal-nuclease digestion

Abstract: [32P]Pi was administered to rats (5mCi/rat) 2h before the isolation of liver nuclei. The isolated nuclei were subjected to mild micrococcal-nuclease digestion for 2.5, 5 and 10 min at 37 degrees C, and the mononucleosomal fraction was subsequently isolated by sucrose-density-gradient centrifugation. The specific radioactivity of 32P-labelled mononucleosomal fractions decreased with increased digestion times. A phosphorylated chromosomal protein, B2 (Mr 68000, pI6.5-8.2), was demonstrated immunologically in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In a previous study we described the production of a polyclonal antibody to a rat liver nuclear phosphoprotein (B2: Mr 68000, pI6.5-8.2) (Zhao & Liew, 1982). This non-histone chromosomal structure and subsequently demonstrated to be preferentially associated with actively transcribed nucleosomes (Liew & Chan, 1976;Chan & Liew, 1977, 1979Liew et al, 1984a). In the present report we carried this immunological approach one step further with the production of several monoclonal antibodies to this phosphoprotein.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…In a previous study we described the production of a polyclonal antibody to a rat liver nuclear phosphoprotein (B2: Mr 68000, pI6.5-8.2) (Zhao & Liew, 1982). This non-histone chromosomal structure and subsequently demonstrated to be preferentially associated with actively transcribed nucleosomes (Liew & Chan, 1976;Chan & Liew, 1977, 1979Liew et al, 1984a). In the present report we carried this immunological approach one step further with the production of several monoclonal antibodies to this phosphoprotein.…”
mentioning
confidence: 85%
“…The relationship between this protein and the phosphoprotein B2 has yet to be determined. Our previous work using regenerating liver as a model system (Liew et al, 1984a) showed that the phosphoprotein B2 showed a maximum phosphorylation at 16 h post-hepatectomy, approximately the same time that DNA synthesis was initiated (Mayfield & Bonner, 1972;Liew & Gornall, 1975). The significant change in the phosphorylation of phosphoprotein B2 following mild micrococcal nuclease digest (5-10% of DNA rendered soluble) (Liew et al, 1984a) suggest that determination of its level in the nucleus may be pertinent in determining its role in actively transcribed chromatin.…”
Section: Determination Of Phosphoprotein B2 By Radioimmunoassaymentioning
confidence: 98%
See 3 more Smart Citations